Influência de diferentes ácidos graxos sobre parâmetros comportamentais e oxidativos em ratos submetidos ao estresse agudo - Pase, Camila Simonetti (2013)
The fatty acids (FA) are important constituents of brain phospholipid membranes and play important roles in the central nervous system (CNS) may modify the plasticity and fluidity, and act decisively in the development of cognitive and neuropsychiatric disorders. During the last decades, we observed changes in eating habits, which enabled increased consumption of trans fatty acids at the expense of consumption of polyunsaturated fatty acids (PUFA), especially omega-3. Furthermore, frequent situations of stress due to pressure of the outside world may also be associated with the development of diseases involving CNS and changes in metabolic function, particularly in the metabolism of fatty acids. In this study, two sequential generations of rats were supplemented with soybean oil (C-SO), fish oil (FO) and hydrogenated vegetable fat (HVF) during pregnancy and lactation. At 41 days of age, half of the male animals of each group were exposed to acute stress (AE-2h) and evaluated in the open field and elevated plus maze, followed by euthanasia for biochemical analysis. The HVF supplemented group had higher anxiety symptoms, while groups C-SO and FO did not show these behaviors. Among the groups exposed to AE, the HVF showed greater locomotion and symptoms similar to anxiety, but this was not observed in the FO. Biochemical analyzes showed higher levels of lipid peroxidation and reduced cell viability in the cortex of HVF group. Furthermore, the HVF treated rats showed reduced catalase activity in the striatum and hippocampus, and increased generation of reactive species in the striatum, while FO was associated with increased cell viability in the hippocampus. Among the groups exposed to AE, the HVF group showed increased generation of reactive species in the brain, decreased cell viability in the cortex and striatum, and decreased catalase activity in the striatum and hippocampus. The results show that the presence of FA for the development and growth over two generations is capable of modifying parameters of oxidative status and behavior of the brain. Taken together, our data support the idea that regular consumption of a diet rich in monounsaturated fatty acids (MUFA) and PUFA, and particularly low in processed foods, can help prevent the development of emotional disorders, and suggest the influence harmful consumption of trans fat over generations, which is able to increase parameters of emotion and nervousness after stressful situations of everyday life can trigger neurological and neuropsychiatric conditions more severe.